Symposium 8: Experiencing the University Context - Wigforss, Eva; Booth, Shirley (Proceedings of the International Conference on Networked Learning, 2006)
Our problem is how to design, with the use of distance and ICT, an appropriate academic context for learning, for students with no previous knowledge of this context. Our aim is to analyse and describe the learner’s relation to the object of his/her studies as part of his/her relation to the learning activity. By using a combination of a phenomenographic approach and activity system theory, we analyse how students experience the learning environment in the extended university. Our results are based in the learner’s perspective. A new methodological approach, using the techniques of creating an intersubjective field, is discussed at the end of the paper.